An Efficient Anti‐poisoning Catalyst against SOx, NOx, and POx: P, N‐Doped Carbon for Oxygen Reduction in Acidic Media. (18th October 2018) - Najam, Tayyaba; Shah, Syed Shoaib Ahmad; Ding, Wei; Jiang, Jinxia; Jia, Li; Yao, Wang; Li, Li; Wei, Zidong
Abstract: Electrocatalysts are readily poisoned during the catalysis of the oxygen reduction reaction (ORR); even air containing traces of SO x and/or NO x significantly decrease the activity and the durability of H2 –O2 fuel cells. Now, a metal‐free strategy is reported to develop an efficient anti‐poisoning ORR catalyst, which involves the pyrolysis of PDAP‐phytic acid super‐molecular aggregate (PPSA). The pyrolyzed co‐doped carbon acting as a metal‐free electrocatalyst shows an enhanced activity for ORR in acidic medium, even under poisoning conditions (SO x, NO x, and PO x ). Moreover, P‐doping also changes the ORR pathway by yielding less than 4 % of H2 O2, indicating a four‐electron pathway whereas more than>20 % of H2 O2 was recorded for N‐doped carbon synthesized from PDAP.